Accounting for the Great Recession in the UK: Real Business Cycles and Financial Frictions - Jagjit S. Chadha; James Warren (University of Kent, School of Economics, 2012)
Using the business cycle accounting (BCA) framework pioneered by Chari, Kehoe and McGratten (2006) we examine the 2008-09 recession in the UK. There has been much commentary on the financial causes of this recession, which we might have expected to shock the equation governing the intertemporal rate of substitution in consumption. However, the recession appears to have been mostly driven by shocks to the efficiency wedge in total production, rather than the intertemporal consumption, labour or spending wedge. From an expenditure perspective this result is consistent with the observed large falls in both consumption and investment during the recession. To assess this result we also simulate artificial data from a DSGE model in which asset price shocks dominate and find no strong role for the intertemporal consumption wedge using the BCA method. This result does not imply that financial frictions did not matter for the recent recession but that such frictions do not necessarily impact only on the intertemporal rate of substitution in consumption.
Keywords: E31; E40; E51; 330; Business Cycle Accounting; Major Recessions; TFP; Financial Frictions